HORMONARY REPLACEMENT THERAPY - Alum, Iqbal; Khan, Alam; Shagufta, Shagufta; Nisa, Aziz -un-; Begum, Nazakat (Journal of Ayub Medical College Abbottabad, 2000)
Menopause is defined as permanent cessation of menstruation and the mean age of menopause in United States is 51 years, with a normal distribution curve and 95% confidence limits between the ages of 45 and 55 years. At this age only a few primordial follicles are left and hence the production of estrogens by ovary is decreased. These small amounts of estrogens cannot cause surge of LH and FSH essential for ovulation. When ovulation does not occur, corpus luteuin is not formed and there is no secretion of estrogens and progesterone. Due to this weak, negative feedback effect of estrogen and progesterone production of LH and FSH increases and so regular cycles disappear. It is found that steroid hormones (estrogen and progesterone) are decreased and gonadotrophins (LH and FSH) are increased after menopause. These findings are important from the diagnostic point of view. These hormonal changes begin about 5 years before the actual menopause. These changes lead to the symptoms like hot flushes, vaginal atrophy, depression, anxiety, memory loss and nervousness. Estrogen deficiency also results in an increased risk of cardiovascular disease and an accelerated loss of bone mass, causing an increased risk of fractures. The leading cause of death in women is cardiovascular disease. Estrogen replacement therapy relieves these symptoms and allows the patients to sleep better.